Water-resource development: the economics of project evaluation - Eckstein, Otto. (Cambridge, Harvard University Press, 1958)
This book examines the federal water resource program in U.S. It analyzes the procedures for measuring benefits and costs employed by the two major agencies which are building federal water resource projects- the Bureau of Reclamation of the Department of the Interior and the Corps of Engineers, U.S Army. The analysis is based on the theory of welfare economics, it treats benefit cost analysis as a means of testing the quality of a project.
Includes index
Includes bibliographical references: p. 283-290.
usc 22/01/2019
Loans
Keywords: Water resources development; United States